2007
DOI: 10.1097/mlg.0b013e318030e422
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms in Ear, Nose, and Throat Infections: How Important are They?

Abstract: As the role of biofilms in human infection becomes better defined, ENT surgeons should be prepared to deal with their unique and tenacious nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 88 publications
1
74
1
1
Order By: Relevance
“…Bacterial biofilms on the middle-ear mucosa are associated with chronic otitis media (Fergie et al, 2004;Vlastarakos et al, 2007). Further, M. catarrhalis is an important aetiological agent of otitis media in children that has been shown to be capable of forming such biofilms (Pearson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial biofilms on the middle-ear mucosa are associated with chronic otitis media (Fergie et al, 2004;Vlastarakos et al, 2007). Further, M. catarrhalis is an important aetiological agent of otitis media in children that has been shown to be capable of forming such biofilms (Pearson et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Two key factors have been linked with suboptimal outcomes in treating such invasive S. aureus infections: (i) the organism's abilities to develop resistance to multiple antibiotics (e.g., methicillin-resistant S. aureus [MRSA] (3), and (ii) its ability to form biofilms on both native tissues and implanted biomaterials (2). It is well known that S. aureus cells within a complex biofilm matrix are refractory to both systemic antimicrobial agents and host immune responses (4)(5)(6).…”
mentioning
confidence: 99%
“…Systemic antibiotic therapy is effective in eliminating circulating bacteria, but it usually fails to protect the surfaces of materials from colonisation, leaving the patient at continued risks of complications or recurrence. [4][5][6][7] In several series, it has been shown that an indwelling DJ ureteral stent carries a significant risk of bacteriuria and stent colonisation. The relationship between urine and stent cultures is not clear, although Lojanapiwat [8] published urine culture results indicating colonisation in about two to three of the patients.…”
Section: Discussionmentioning
confidence: 99%